A study on knowledge, attitude and practices towards research among medical post graduate students - Junga, Tejaswini; Naidana, Partha Sarathy (International Journal Of Community Medicine And Public Health, 2024)
Background: Research is crucial for the scientific progress of the health of individuals and communities. Understanding the concept of evidence-based medicine needs strong research knowledge. Research assures understanding of the subject and improves the knowledge of the students. This study was aimed to assess the level of knowledge, attitude and practices among medical post graduate students and to study the sociodemographic factors. And to determine the association of knowledge with various sociodemographic factors. Methods: An analytical cross-sectional study conducted during a period of two months among the medical post graduate students studying in a private medical college. Knowledge, attitude and practice were assessed by using self- administered questionnaire among 117 post graduate students. Likert scale was used to assess the knowledge component. Results: Among 117 study subjects 47% were first year 27.4% were second year and 25.6% were third year among which the overall adequate knowledge was 86.3%, positive attitude was 95.7% and good practices according to the study scale was only 29.1%. Level of knowledge and practices were found to be having significant association with the academic year studying in (p value <0.05). Conclusions: The post graduate students had adequate knowledge and positive attitude but had poor practices towards research. Adequate research helps to bridge the gaps in research and help the future generations in developing new interventions.